A protocol for managing dissociative symptoms in refugee populations. (2019) - Chessell, Zoe J.; Brady, Francesca; Akbar, Sameena; Stevens, Adele; Young, Kerry
Abstract: This article describes a clinical protocol for supporting those presenting with post-traumatic stress disorder (PTSD) and dissociative symptoms, particularly dissociative flashbacks, based on a cross-culturally applicable model. The protocol is discussed from the perspective of working with a refugee and asylum seeker population, although many of the principles will be applicable to clients from any background presenting with these dissociative symptoms. The protocol addresses the assessment and formulation of a client's dissociative symptoms. It includes guidance on sharing psycho-education with clients regarding the evolutionary function of dissociation and developing practical strategies to monitor and manage dissociative symptoms. The strengths and limitations of this protocol are also discussed. Key learning aims: After reading this article people will: (1) Be able to understand a cross-culturally applicable model of dissociation and how it applies to clinical practice when working with clients presenting with dissociative symptoms, particularly dissociative flashbacks, in the context of a diagnosis of PTSD. (2) Be able to assess and formulate dissociative symptoms as part of an overall PTSD formulation. (3) Be able to develop practical strategies for assisting clients in monitoring and managing their dissociative symptoms. (4) Be familiar with adaptations for using this approach with refugee and asylum seeker populations.